Enhancing Arab learners’ EFL Linguistic Accuracy through Technology Integration in an Omani Context - Jose, Jayaron (Advances in Social Sciences Research Journal, 2021)
Integration of technology especially ICT (Information and Communication Technologies) has been inevitable in the field of ELT for over many decades across the globe in general, and Arab world and Sultanate of Oman in particular. In line with the increasing trend of technology use in ELT, the study was conducted to determine the effectiveness of technological integration in improving students’ linguistic accuracy in writing in EFL classrooms in Oman. The experimental study was administered for a period of one semester among 56 students (N=56) at University of Technology and Applied Sciences, Al Musanna (UTAS-A) in Oman by means of online blog and forum treatments. The students were divided in to two groups – blog group (N=28) and forum group (N=28). While the former engaged themselves in online Blog writing asynchronously, the latter involved in online forum writing (discussions) synchronously. The learners’ performance was assessed through a pre-test and a post-test; an interview was administered to gauge the qualitative aspect of the study; consequently, the quantitative and qualitative data was analysed statistically. Therefore, study has concluded that EFL linguistic accuracy of students treated with online forum and blogs improved over time, and forum group demonstrated better performance than blog group.